1996
DOI: 10.1097/00005392-199604000-00040
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Semen After Extracorporeal Shock Wave Lithotripsy for Lower Ureteral Stones

Abstract: The in vivo and in vitro examinations demonstrated deterioration in semen quality. Sperm density and sperm motility returned to normal 3 months after ESWL, indicating at least a transitory decrease in male fertility may occur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…In the past 20 years, the biologic effects of SWL have been intensively investigated (10)(11)(12)(13). In some of these studies, it was reported that shock waves applied at a therapeutic level of energy may cause double-strand DNA damage (12,13).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the past 20 years, the biologic effects of SWL have been intensively investigated (10)(11)(12)(13). In some of these studies, it was reported that shock waves applied at a therapeutic level of energy may cause double-strand DNA damage (12,13).…”
Section: Discussionmentioning
confidence: 99%
“…Although clinical and experimental investigations have suggested the safety of SWL, its possible effects on the male reproductive system are still not known. Furthermore, the literature contains a limited body of research with contradictory results on the possible effects of SWL on semen characteristic and gonads (10,11,(14)(15)(16)(17)(18)(19). Although Puppo et al (16) reported no adverse effect on male fertility, Andreessen et al (10) noted macroscopic and microscopic hemospermia and decreased sperm motility and sperm density.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In men, distal ureteral ESWL has been shown to cause a transient but reversible impairment in semen quality [46,47,48]. Both microscopic and macroscopic hemospermia can be seen, as well as decreased sperm density and motility.…”
Section: Is Eswl For Ureteral Stones Safe?mentioning
confidence: 99%
“…The testes may be exposed to shock waves when ESWL is used to treat stone disease in the lower ureter and bladder. However, there is still controversy concerning the effects of shock waves on the testes and on male fertility (4,7). In this study, we investigated the in vivo effects of shock waves applied to the pelvic region on testicular histopathology and sperm morphology.…”
mentioning
confidence: 99%